Long-term muscle changes after hamstring lengthening in children with bilateral cerebral palsy - Salami, Firooz; Klotz, Matthias C. M.; Dreher, Thomas; Wolf, Sebastian Immanuel (Developmental medicine and child neurology, 2019)
Aim To evaluate short-term (1y postoperatively; E1) and long-term (at least 4y postoperatively; E2) changes in hamstring muscle-tendon length (MTL) and lengthening velocity after hamstring lengthening in children with bilateral cerebral palsy (CP). Method Three-dimensional gait analysis was performed in 19 children (16 males, 3 females; 36 limbs; mean age at surgery 9y [SD 3y]; range 6-10y) with flexed knee gait, preoperative ankle dorsiflexion lower than 20 degrees, and CP before bilateral hamstring lengthening (E0), at E1 and E2. Hamstring MTL (normalized by leg length) and velocity were assessed via OpenSim software. Results MTL increased from E0 to E1 (p=0.004) and decreased from E1 to E2 (p<0.020). Hamstring lengthening velocity did not change. In the subgroup with short, not slow hamstrings, the increase in MTL was maintained at E2. Interpretation Hamstring lengthening is an efficient procedure to lengthen short and/or slow hamstrings short-term. The desired outcome with maintenance of the postoperative changes in hamstring MTL is only achieved for preoperatively short, not slow hamstrings. What this paper adds Surgical hamstring lengthening can be confirmed via musculoskeletal modelling in OpenSim software. Surgical hamstring lengthening in cerebral palsy does not change hamstring lengthening velocity. Short, not slow hamstrings present a long-lasting muscle-tendon length (MTL) increase after hamstring lengthening. Changes in MTL after hamstring lengthening cannot be maintained for slow hamstrings. MTL does not change after hamstring lengthening for neither short nor slow hamstrings.
Gesehen am 15.05.2019